PERAN APLIKASI CORETAX DALAM PENGELOLAAN PERUBAHAN STATUS WAJIB PAJAK PADA PROSES BISNIS REGISTRASI DI KPP PRATAMA MATARAM TIMUR - Wardiningsih, Reny; Arfiani Ramadhan, Mentari; Adriani Auliana, Rini (Jurnal Aplikasi Perpajakan, 2025)
Changes in taxpayer status constitute an essential component of tax administration, as they directly affect the accuracy of taxpayer data and the quality of tax services. This study aims to analyze the role of the Coretax application in managing taxpayer status changes within the Registration Business Process at the East Mataram Primary Tax Office (KPP Pratama Mataram Timur). Coretax is an information system developed by the Directorate General of Taxes to support the automation and integration of tax administration processes, including taxpayer registration and data updates. This research employs a qualitative descriptive method, with data collected through observation, interviews with tax office personnel, and documentation studies. The results indicate that Coretax plays a strategic role in accelerating taxpayer data modification processes, enhancing information accuracy, and promoting transparency and accountability in service delivery. The system effectively minimizes manual errors and shortens service processing time, thereby improving the efficiency of registration officers’ workflow. Nonetheless, several challenges remain, including system capacity limitations, network disruptions, and the need to strengthen human resource competencies to optimize the use of system features. Overall, the application of Coretax has been shown to make a positive contribution to improving the quality of taxpayer registration processes at the East Mataram Tax Office. This study recommends improving technological infrastructure and providing technical training for personnel to maximize the comprehensive utilization of the Coretax system.